Human Resource for Health Production Capacity in Nepal: A Glance - Gupta RP, Ghimire J, Kumal AB, Mahato RK (Journal of Nepal Health Research Council, 2013)
Background: Shortage of human resources for health is apparent in Nepal. The current HRH strategy has tried to address the demand for skilled birth attendants, MDGPs, Gynecologists, Anesthetists, Radiologists and other health workforce. Despite the increased number of institutions, there is still shortage of health workforce due to ineffective monitoring. This study was undertaken to find out the situation of HRH production in Nepal.Methods: This cross sectional study was conducted from September 2012 to February 2013. The primary focus was on the quantitative method by using the format for the data collection. The main study samples were the academic institutions of Nepal. The finding was analyzed and tabulated in the summary form.Results: There were a total of 294 institutions to produce different cadres of health workforce in Nepal. Staff nurses (101) and CMAs (76) have been produced by the maximum number of institutions. The result revealed that the institutions were not producing the graduates upon their capacity, only 1,451 staff nurse graduated annually against the capacity of producing 4,017 per annum. Although Nepal has a capacity to produce 1,760 MBBS, 267 MD and 116 MS doctors, only 1,074 Nepali MBBS, 222 MD and 95 MS doctors graduated per year.Conclusions: The health institutions performance is lower in producing HRH compared to their capacity in the country. A long-term effort is now required to match demand and supply of the HRH in the country.